Conversing and conforming : small business owners’ lived experiences of family communication patterns in their youth : a reflexive thematic analysis : a thesis presented in partial fulfilment of the requirements of the degree of Master of Business Studies in Communication at Massey University, Palmerston North, New Zealand - Fordyce, Natalia (Massey University, 2024)
Small businesses are critical to the healthy functioning of the New Zealand economy. Due to the scale of these businesses, owners are typically heavily involved in the operations of their business. There is significant value in understanding the lived experiences of small New Zealand business owners during their formative years, as this contributes greatly to how they perceive and interact with the world today. However, limited research to date has been concerned with the childhood experiences of small business owners, and even less exists in a New Zealand context. Using Family Communication Patterns (FCP) theory, this study aims to address this gap by asking how the family communication patterns experienced in early life may have impacted on the lived experiences of small New Zealand business owners. Taking a qualitative approach to this often quantitatively geared theory, a phenomenological theoretical framework was engaged while using reflexive thematic analysis (RTA) to explore the lived experiences of eight small business owners. These business owners live and were raised in New Zealand, and now own businesses of less than 20 staff, placing this study in a uniquely New Zealand context. Through enacting RTA, six themes were generated from the small business owners’ experiences: (1) Independence from an Early Age, (2) Religiosity and Associated Values, (3) Nuanced Family Dynamics, (4) Conforming to Authority, (5) New Zealand: An Emotionally Guarded Culture, and (6) Rejecting or Emulating Family Practices. The findings depict the lived experiences of small business owners to be characterised by independence from an early age, which is tied into resilience built from overcoming adversity, as well as problem solving and self-efficacy. Also indicated in the findings is the important grounding of religiously oriented family communication, as well as the culturally situated discomfort individuals feel disclosing their feelings and emotions. Finally, it is evident that childhood experiences of family communication continue to have a great impact in the lives of the small business owners today.
Keywords: 350716 Small business organisation and management; 520503 Personality and individual differences